Sudden death from systemic sarcoidosis: a case of legal medicine - Zoja, R.; Andreola, S.; Gentile, et al., G. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Introduction: The sarcoid condition of vital organs such as heart, lungs, liver and brain, may constitute, though rarely, a dangerous situation for survival. In forensic pathology, sudden death related to such disease represents an unusual event occurring in subjects who die unexpectedly in spite of their previous good health, and whose autopsy reveals, mainly, the involvement of heart or the central nervous system (CNS). The case: The Authors describe a case of sudden death due to systemic sarcoidosis with atypical presentation in a young South American nulliparous woman showing, as the only symptom, occasional episodes of spotting during the last two months of her life. Results: The only noteworthy finding from the autopsy resulted in secondary obstructive hydrocephalus. The subsequent forensic toxicological examination was negative, whereas the histopathological examination, conducted by means of post-fixation techniques and standard coloring methods on the viscera removed during autopsy, revealed useful data to determine the cause of death, consisting of a diffuse inflammatory reaction with giant cells and epithelioid cells of sarcoid type localized in the CNS and in the genitourinary apparatus. Conclusions: The case presented, ranking among deaths occurred unexpectedly, is a useful opportunity both for clinical remarks, given its inherent diagnostic difficulties, especially in the presence of atypical symptoms, and for legal medicine ones, given the inclusion of sarcoidosis in cases of sudden death that can give rise to criminal investigations.